An ideological analysis of the construction of masculinity in the South African superhero comic book, Kwezi - Reyneke, Brendon George (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2020)
In 2014, South African artist and comic book illustrator, Loyiso Mkize created Kwezi, South Africa's first superhero comic book. His comic features the titular Kwezi as a young, black man living alone on the outskirts of Gold City who discovers he has superpowers. Along with Kwezi, the comic is populated by predominantly black African characters "“ both good and bad. The creation of Kwezi is an important step in the development of comic books in South Africa as it draws from the cultural and physical landscape of the country and speaks to young black people without them having to look outside of the country for superheroes to identify with. Stuart Hall (Hall, 1997, pp. 272-274) asserts that attempts to reclaim the black subject in popular culture tend to go through two phases. In the first phase blackness is liberated from negative representations and is replaced with more positive depictions. Thereafter though, the black subject is produced inside contemporary "regimes of representation" . In this thesis, I will show how Mkize's representation of Kwezi follows Stuart Hall's description of the reclamation of black subjectivity. Using narrative theory, visual social semiotics and Thompson's modes of operational ideology I will show how in his attempt to represent African blackness positively, Mkize overlooks normative genre representations of masculinity and produces a story of a South African that remains unliberated from patriarchy and hegemonic masculinity. Mkize reproduces many of the hegemonic discourses concerning the masculine body, the power difference between male and female characters and subscribes to the justified, violent actions of the masculine superhero. Typically, in superhero comics there is an erasure of the ordinary man in favour of an excessive and powerful one-dimensional masculine ideal (Brown, 1999, pp. 31-32) At the end of my analysis I will show that Kwezi is constructed in this way as a physically strong and muscular, violent and emotionless, self-made man who is in control and overcomes all obstacles.
Keywords: Mkize, Loyiso, 1987- -- Kwezi; Superheroes -- South Africa; Comic books, strips, etc. -- South Africa; Graphic novels -- South Africa; Masculinity in literature; Violence in literature; Superheroes, Black